Miscibility Studies on a Copolyester of Bisphenol-A with Terephthalic and Isophthalic Acids/Bisphenol-A Polycarbonate Blends - Sakar, Dolunay; Cakar, Fatih; Cankurtaran, Ozlem; Karaman, Ferdane (WILEY, 2010)
The miscibility behavior of the blends of a copolyester of bisphenol-A with terephthalic and isophthalic acids (PAr) and a bisphenol-A polycarbonate (PC) was studied in dilute chloroform solutions at 25 degrees C. The intrinsic viscosity and Huggins' parameter of the binary mixtures were determined from the intercept and slope of the linear straight line between specific viscosity and the overall polymer concentration at the studied compositions. From experimental results of the intrinsic viscosities of the mixtures, some miscibility parameters Delta b, Delta b', (Delta b)(G), Delta[eta], alpha, and beta were obtained by applying the criteria proposed by the research groups Krigbaum and Wall, Catsiff and Hewett, Garcia et al., Sun et al. and Jiang and Han, respectively. The miscibility of mixtures was also studied by using differential scanning calorimetry and fourier transform infrared spectroscopy. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 309-314, 2010
Keywords: bisphenol- a polycarbonate; Polyarylate; blends; miscibility; viscosity; POLYMER; POLYSTYRENE; CRITERION; STATE; ACIDS; Polymer Science